If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50m + 2y = 7y Solving 50m + 2y = 7y Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2y' to each side of the equation. 50m + 2y + -2y = 7y + -2y Combine like terms: 2y + -2y = 0 50m + 0 = 7y + -2y 50m = 7y + -2y Combine like terms: 7y + -2y = 5y 50m = 5y Divide each side by '50'. m = 0.1y Simplifying m = 0.1y
| -4x+-2+6=9 | | 4x+-2x+6=9 | | 2x+4=5x+9 | | -9(x-1)=-36 | | 8=1-2n+5 | | 5/3w-7/4=-w-4/3 | | -6-3x=27 | | -45=9(-2+x) | | -4x+18=-6 | | -x+x-4=2 | | -3p=-27 | | 5a^2=25a | | 4w-5(2w-6)=10-(w-5) | | -0.6b+7+0.4b=19 | | x^2+y^2+10x+6y+34=0 | | 176=-16m | | -10(x-6)=70 | | x^2+y^2+10x+6y=-34 | | -8h+47=-1 | | x^2+y^2=-10x-6y-34 | | -15x+22=-38 | | 45+2(3-x)=2 | | 11-8z=69 | | (2x^2-11x-15)/(x+7) | | 4q-17=17 | | 2q+9=5 | | (x-y-1)dx+(4y+x-1)dy=0 | | 6=18-4x | | 2(3y-4)=3(y-2/3) | | -4+0= | | 10+14y=-130 | | 8-2x=2x-4 |